2013
DOI: 10.1175/jtech-d-12-00168.1
|View full text |Cite
|
Sign up to set email alerts
|

Design and Sampling Characteristics of a New Airborne Aerosol Inlet for Aerosol Measurements in Clouds

Abstract: Design of a new submicron aerosol inlet (SMAI) for airborne sampling of aerosol particles is introduced and its performance characteristics under a range of sampling conditions are presented. Analysis of inlet performance in clear-air and cloud systems shows that submicron aerosols are sampled representatively by the inlet, and in comparison with other types of inlets the SMAI has a relatively minor or nonexistent problem of droplet shatter contamination. The SMAI has a flow-through cone, with a perpendicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…The sample flow was extracted from the flow-through tube at an angle of ∼ 80 • , ensuring that only particles smaller than a cut size will be sampled. The sampling efficiency of such a cross-flow sampling inlet is largely determined by the size of the flow-constricting nozzle (Craig et al, 2013b). Using 3-D CFD simulations, the appropriate size of the flowconstricting nozzle required for a 2 µm sampling cut size was determined.…”
Section: Base-iimentioning
confidence: 99%
See 3 more Smart Citations
“…The sample flow was extracted from the flow-through tube at an angle of ∼ 80 • , ensuring that only particles smaller than a cut size will be sampled. The sampling efficiency of such a cross-flow sampling inlet is largely determined by the size of the flow-constricting nozzle (Craig et al, 2013b). Using 3-D CFD simulations, the appropriate size of the flowconstricting nozzle required for a 2 µm sampling cut size was determined.…”
Section: Base-iimentioning
confidence: 99%
“…Enhancement values greater than 1 are usually indicative of shatter artifacts in CN measurements (Craig et al, 2013b). To facilitate a direct comparison of the performance of the two BASE designs, the BASE CN enhancement values were normalized using CN enhancements from the SMAI as a reference sampler.…”
Section: Cn Measurements In Warm Cloudsmentioning
confidence: 99%
See 2 more Smart Citations
“…Observations from Craig et al (2013b) and Weber et al (1998) showed that enhancements of aerosol concentrations were greater in warm liquid clouds than in cold ice clouds. Observations from Craig et al (2013b) and Weber et al (1998) showed that enhancements of aerosol concentrations were greater in warm liquid clouds than in cold ice clouds.…”
Section: Introductionmentioning
confidence: 99%